Bibliometric Review of Research Trends in Artificial Intelligence in Education - Hasan, Moh. Ferdi (Proceeding International Conference on Religion, Science and Education, 2024)
This study provides an overview of research trends in the application of Artificial Intelligence (AI) in education over the period 2019-2023. Through a bibliometric review of 3000 publications in the Scopus database, we identified several key focus areas including personalization of learning, data mining, and ethical and practical challenges in the application of AI in education. Results show a growing interest in these topics with an increasing number of publications each year. While this study provides important insights, there are limitations such as limited data sources on Scopus and challenges in classifying and interpreting certain data. The findings show potential for further research on how to apply AI in education as well as implications for educational practitioners.